HEART AND LUNG FAILURE, TRANSPLANTOLOGYThe impact of chronic kidney disease on the annual prognosis in patients 80+ years old suffering from chronic heart failure - Cichocka-Radwan, Anna; Ciurus, Tomasz; Lelonek, Malgorzata (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2014)
Introduction : It is well known that the function of kidneys is impaired with age. Aim: The purpose of the study was to evaluate whether chronic kidney disease (CKD) is a predictor for 1-year follow-up mortality among hospitalized chronic heart failure (CHF) patients aged 80+. Material and methods : The study included 141 consecutive patients aged 80-92 (mean: 82.4 years, 44.7% men). The prospective analysis contains 61 variables with glomerular filtration rate (GFR) and the occurrence of death at the 1-year follow-up. Patients were divided and analyzed depending on GFR. Results : Chronic kidney disease defined as estimated GFR < 60 mL/min/1.73 m 2 was recorded in 93 patients (66%). A relationship with GFR < 60 was found for older age (p = 0.0001), lower BMI (p = 0.003), more advanced NYHA class III (p = 0.007), higher concentrations of NT-proBNP (p = 0.023), lower hemoglobin (p = 0.0004) and LVEF (p = 0.005), longer hospitalization (p = 0.005), more frequent ventricular blocks in ECG (p = 0.017) and rarely performed coronary angiography (p = 0.021). In turn, GFR < 30 ml/min/1.73 m 2 was recorded in 14 patients (9.9%). Similar relationships as in GFR < 60 were found for GFR < 30 and additionally higher concentrations of high-sensitivity C-reactive protein (hsCRP) (p = 0.003), D-dimer (p = 0.002) and more frequent dyslipidemia (p = 0.004) and left main coronary artery disease (p = 0.007). Annual mortality for the total population was 14.2% (n = 20) and was higher (16.1%) if GFR was < 60 and even more (21.4%) in GFR < 30. However, the relationship between deaths and GFR was not statistically significant (for GFR < 60, p = 0.505 and GFR < 30, p = 0.547). Conclusions : Annual mortality in the patients 80+ who suffered from CHF was high but not statistically significantly associated with CKD.